Effect of ultrasonic post-treatment on anaerobic digestion of lignocellulosic waste. Issue 2 (February 2021) - Boni, Maria Rosaria; Polettini, Alessandra; Pomi, Raffaella; Rossi, Andreina
This paper evaluates the effects of ultrasonication (US) applied, individually or in combination with a mechanical treatment, to the effluent of anaerobic digestion (AD) of lignocellulosic waste, on methane (CH4 ) production. US of the substrate downstream of AD is a relatively novel concept aimed at improving the degradation of recalcitrant components in order to enhance the overall energy efficiency of the process. US tests were carried out on real digestate samples at different energies (500−50, 000 kJ/kg total solids (TS), corresponding to sonication densities of 0.08−0.45 W/ml). AD tests were performed on mixtures of sonicated (Sus ) and untreated (S) substrate at two different Sus : S ratios (25:75 and 75:25 w/w), simulating post-sonicated material recycling to the biological process. The US effect was estimated through the solubilization degree of organic matter, as well as the CH4 production yield and kinetics, which were all found to be enhanced by the treatment. At Sus : S = 75:25 and Es ≥ 20, 000 kJ/kg TS (0.25 W/ml), CH4 production improved by 20% and the values of the kinetic parameters increased by 64–82%.